ELEVATED CO2 AND WATER DEPTH REGULATION OF METHANE EMISSIONS: COMPARISON OF WOODY AND NON-WOODY WETLAND PLANT SPECIES - Vann Ch.D.; Patrick Megonigal J. (My University, 2003)
Elevated CO2 has been shown to increase methane emissions in herbaceous wetlands, but it is not clear that this will occur in wetlands dominated by woody plants or in wetlands that are not inundated. We determined the effects of elevated CO2 and water table position on methane emission and oxidation rates from plant-soil microcosms planted with a woody tree, Taxodium distichum, or an emergent aquatic macrophyte, Orontium aquaticum. Experiments were conducted in replicate glasshouses (n = 2) at CO2 concentrations of either 350 or 700 ppmv. Plants were grown from seed and subjected to two water level depths, flooded (+5 cm above the soil surface) and non-flooded (-10 cm for T. distichum and -6 cm for O. aquaticum). Elevated CO2 increased whole-plant photosynthetic rates in both water table treatments. Methane emission rates increased by 62 to 69% in the T. distichum treatment and 27 to 29% in the O. aquaticum treatment. Whole-plant photosynthesis and biomass were strongly correlated with methane emissions (r2≥ 0.75, P ≤ 0.01). This relationship provides evidence of a tight coupling between plant and microbial activity and suggests that similar relationships from other wetland studies measured at ambient CO2 can be extrapolated into the future. In the O. aquaticum, non-flooded treatment, methanotrophy consumed 14 and 22% (replicate glasshouses) of the methane produced in the ambient treatment compared to 29 and 36% in the elevated CO2 treatment. However, there was no significant methane oxidation detected in the flooded treatment. We concluded that woody and non-woody wetland ecosystems growing in a future CO2-enriched atmosphere will emit more methane regardless of water table position, but the degree of stimulation will be sensitive to changes in water table position, particularly in forested wetlands.
Keywords: ELEVATED CO2; GLOBAL CHANGE; METHANE EMISSIONS; METHANE OXIDATION; PRODUCTIVITY; TAXODIUM DISTICHUM; WETLANDS